Waste Management Among the Residents of Village Tagunbanhan, Ajuy, Iloilo, Philippines - Alimen, Rolando A.; Jaleco, Victor B.; Lacuesta, Jose Marie (JPAIR Multidisciplinary Research, 2009)
This study determined the level of knowledge in waste management among residents of Village Tagunbanhan, Ajuy, and Iloilo. The participants were 30 purposively selected residents of Village Tagunbanhan, Ajuy, and Iloilo. The quantitative-qualitative method of analysis was utilized in this study. The data were gathered through the use of questionnaire developed by the researchers. Interview was also employed to gather the qualitative data. As an entire group, the level of knowledge in waste management among residents of Village Tagunbanhan, Ajuy, Iloilo was "high level of knowledge" as an entire group and when classified according to different categories.
Keywords: waste management; environment; community service